Community-Acquired Pneumonia (CAP) in HIV Patients - Arimbi, Muzaijadah Retno (Syntax Corporation Indonesia, 2025)
CAP continues to be a significant infectious disease among individuals living with HIV, even in the era of ART. HIV-positive individuals are at heightened risk for CAP due to altered immune function and exposure to a broader range of potential pathogens compared to the general population. This study aimed to examine the clinical characteristics, causative agents, and outcomes of CAP in HIV-infected patients to inform more accurate and evidence-based management practices. A descriptive qualitative approach was employed, with data obtained from various documented sources relevant to the topic. The analysis process followed the three-step model by Miles and Huberman, which includes data reduction, data display, and conclusion drawing. The findings reveal that HIV-infected patients with pneumonia often present with typical acute symptoms and can be appropriately evaluated using the PSI. Diagnostic and therapeutic procedures were consistent with those used for non-HIV patients, involving chest X-rays, sputum or BAL sampling, and blood tests prior to the initiation of empirical antibiotic therapy. Key strategies such as consistent use of ART, smoking cessation, and vaccination (particularly against pneumococcus and influenza) were found to be critical in both the treatment and prevention of CAP among HIV-positive individuals. Nevertheless, further research is necessary to refine prevention strategies and determine the most effective approaches for long-term disease management in this vulnerable population.